ÁLVAREZ MURO, ALEXANDRA. (2000). Poética del habla cotidiana - Larrauri, Ainoa (Revista Latinoamericana de Estudios del Discurso, 2020)
ÁLVAREZ MURO, ALEXANDRA. (2000). Poética del habla cotidiana. Mérida, Venezuela: Universidad de Los Andes. 225 pp. ISBN: 980-292-862-3.